Percepção docente sobre as práticas pedagógicas e a criança com autismo - Ferreira, Simone Pires (2020)
This research is linked to the research line "Educational Process and Teacher Training of the Graduate Program of the Catholic University of Brasília (UCB)" and to the research "Cartography of Learning Territories as a Strategy for the Reconstruction of Teaching Work (CNPq / UCB)". The central question of investigation is to know the perception of teachers in relation to their pedagogical practices for students with autism, with the objective of understanding how teachers perceive such practices. As for theoretical contributions, it is based on the perspective of Historical-Cultural Theory with Vigotsky as the main exponent and in recent research on children with autism, highlighting the social, educational, linguistic and mediational aspects. As regards the methodological approach is a qualitative research based on cartographic method, using a questionnaire and interviews from a cartographic perspective. The main results indicate that although the majority of teachers present a theoretical-methodological conception consistent with the Historical-Cultural Theory, they reveal through their own perceptions that their practices are still in the process of being built, as well as in some cases, conflict with perspectives of biological accent, contradicting the referred conception. They emphasized the lack of more specialized training to improve their practices with this specific audience, as well as the importance of support from the school community and the student's family.